2021
DOI: 10.3390/ma14237469
|View full text |Cite
|
Sign up to set email alerts
|

Robust Heterojunctions of Metallic Alloy and Carbon Fiber-Reinforced Composite Induced by Laser Processing

Abstract: The development of heterojunctions with a strong bonding interface between metals and non-metals has attracted much attention owing to their great potential for use in lightweight structures. Laser joining technology, which emerged as a fast and reliable method, has proven its feasibility and unique advantages in joining metal to polymer matrix composites. Herein, an optimized laser joining configuration has been employed to realize high-quality joining of titanium alloy and carbon fiber-reinforced composite. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Compared to the joints with grating textures on the Ti6Al4V surface, the joints with grid textures on the Ti6Al4V surface present slightly higher fracture strength, as shown in Figure 5 . In the case of the microgroove width of 265 ± 10 μm, the joints achieved a maximum fracture strength of 58 MPa, which is higher than most previous reported results (10–40 MPa) of laser joined heterojunctions [ 19 , 20 , 21 , 29 , 30 , 31 ], as displayed in Figure 5 . The higher joint strength was mainly attributable to the larger area of the mechanical interlocking structures and the strong adhesion at the joining interfaces.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…Compared to the joints with grating textures on the Ti6Al4V surface, the joints with grid textures on the Ti6Al4V surface present slightly higher fracture strength, as shown in Figure 5 . In the case of the microgroove width of 265 ± 10 μm, the joints achieved a maximum fracture strength of 58 MPa, which is higher than most previous reported results (10–40 MPa) of laser joined heterojunctions [ 19 , 20 , 21 , 29 , 30 , 31 ], as displayed in Figure 5 . The higher joint strength was mainly attributable to the larger area of the mechanical interlocking structures and the strong adhesion at the joining interfaces.…”
Section: Resultscontrasting
confidence: 61%
“…The resultant joint strength between Ti6Al4V and GF30/PA66 improved from 13.8 MPa to 41.5 MPa [ 19 , 20 ]. The influence of structure density on the joint strength between Ti6Al4V and CF30/PEEK was further analyzed, and the obtained joints presented high fracture strength and excellent anti-aging properties, with the largest fracture strength reaching over 60 MPa [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-quality laser joining of CF30/PEEK and Ti6Al4V (2 mm thickness) was achieved by preparing micro-textures of different depths and densities (Figure 8C), using an ultrafast laser system (femtosecond). 39 Tensile tests showed that the joint strength increased with the increase of texture density on the metal surface. With a texture density of >90% and a texture depth of 500 μm, the highest fracture strength of the joint could exceed 60 MPa even after alternating hightemperature and low-temperature aging tests.…”
Section: Laser Welding Of Cfrpt To Titanium Alloysmentioning
confidence: 99%
“…The clamping force is a crucial factor that influences the joint's mechanical properties in laser welding CFRTP/ metal. The continuous clamping pressure can effectively suppress and eliminate microbubbles near the interface, 39 boost the flow of melted plastic, and improve the filling effect of the melted plastic into the micro-texture of the metal surface. However, high pressure leads to an excessive expansion of the resin at the edges and a reduction of the molten resin at the interface, resulting in a gradual decrease in the joint's mechanical performance.…”
Section: Clamping Pressurementioning
confidence: 99%
See 1 more Smart Citation